Development of Electronic Worksheet Based on Project Based Learning using Liveworksheet to Improve Critical Thinking Skills - Nora ulfiah; Desy Hanisa Putri; Iwan Setiawan (Jurnal Penelitian Pembelajaran Fisika, 2025)
The purpose of this research is to determine the feasibility of developing Electronic worksheet based on Project Based Learning using Liveworksheet and to determine the improvement of students Critical Thinking skills after the implementation of Electronic worksheet based on Project Based Learning using Liveworksheet. The research method used is research and development (R&D) with a development model using the ADDIE model which consists of 5 phases (Analyze, Design, Development, Implementation and Evaluation). The results of the research data were obtained from needs analysis, interview results, observations, validation results of media experts and materials. Based on the results of media validation, it shows that Electronic worksheet based on Project-Based Learning using Liveworksheet gets a percentage of 90.62% with a very feasible category. In the field trial, the N-gain result is 0.62 which is included in the moderate category. Based on the results of the analysis, it can be concluded that the Electronic worksheet based on Project Based Learning using Liveworksheet is very feasible to use.